Thermodynamic Refractory Corrosion Model for Ferronickel Manufacturing - Christoph Sagadin; Stefan Luidold; Christoph Wagner; Christoph Pichler; Daniel Kreuzer; Alfred Spanring; Helmut Antrekowitsch; Amy Clarke; Kester Clarke (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2021)
A thermodynamic model, based on SimuSage, was developed to simulate refractory corrosion between a magnesia-based refractory material and ferronickel (FeNi) slags. The model considers a theoretical cross-section of a refractory material to simulate a ferronickel smelter application. The current model is structured into 10 zones, which characterize different sectors in the brick (hot to cold side) perpendicular to the refractory surface with an underlying temperature gradient. In each zone, the model calculates the equilibrium between the slag and a specified amount of refractory material. The emerging liquid phases are transferred to subsequent zones. Meanwhile, all solids remain in the calculated zone. This computational process repeats until a steady state is reached in each zone. The simulation results show that when FeNi slag infiltrates into the refractory material, the melt dissolves the magnesia-based refractory and forms silicates (Mg,Fe,Ca)2SiO4 and Al spinel ((Mg,Fe)Al2O4). Furthermore, it was observed that iron oxide from the slag reacts with the refractory and generates magnesiowustite (Mg,Fe)O. Practical lab-scale tests and scanning electron microscopy (SEM)/Energy Dispersive X-ray Spectroscopy (EDS) characterization confirmed the formation of these minerals. Finally, the refractory corrosion model (RCM) ultimately provides a pathway for improving refractory lifetimes and performance.
Publisher Copyright: extcopyright 2021, The Author(s).